Merevisi Narasi Orientalis tentang Arabia Pra-Islam: Analisis Qur’ani terhadap Teori Creswell dan Finster - Edi Sutardi (Journal of Innovative and Creativity, 2025)
Orientalist scholarship on pre-Islamic Arabia often reflects an epistemological bias against Arab civilization, particularly in architectural, social, and spiritual dimensions. K.A.C. Creswell, in Early Muslim Architecture (1932), argued that Islam lacked an original architectural identity, merely adapting Byzantine and Persian models. This view constructed the Arabs as culturally void before Islam. Conversely, Barbara Finster, in “The Pre-Islamic Period” (2004), revised this assumption by emphasizing the continuity of material and symbolic traditions across Yemen, Hijaz, and Nabatean territories. This article reexamines both theories through a Qur’anic lens, focusing on verses that affirm pre-Islamic Arab civilization (Q.S. Saba’ [34]:15, Al-Fajr [89]:6–8, and Ad-Dhuhā [93]:7). Using a thematic tafsir and discourse-critical approach, this study argues that the Qur’an portrays Arabia as a land with historical depth, moral consciousness, and monotheistic roots. Consequently, Creswell’s theory requires revision toward a more balanced framework grounded in Qur’anic and Arab primary sources, in line with Finster’s perspective and contemporary Qur’anic studies by Angelika Neuwirth and Nicolai Sinai.